Conditioning equine athletes on water treadmills significantly improves peak oxygen consumption. (29th February 2020) - Greco‐Otto, Persephone; Bond, Stephanie; Sides, Raymond; Bayly, Warwick; Leguillette, Renaud
Abstract : Equine water treadmills (WT) were initially designed for rehabilitation of musculoskeletal injuries, but are also commonly used for conditioning sport horses, however the effects are not well documented. The purpose of this study was to test the effect of an 18‐day WT conditioning programme on peak oxygen consumption (V̇O2 peak). Nine unfit Thoroughbreds were used in a randomised controlled trial. Six horses worked daily for 18 days in stifle‐height water (WT group), while 3 control horses worked without water (dry treadmill group (DT)). Preconditioning and postconditioning maximal exercise racetrack tests (800 m) were performed using a portable ergospirometry system. Measured outcomes were V̇O2, tidal volume, minute ventilation, breathing frequency, heart rate, blood lactate and instantaneous and average speed. The workload as assessed by V̇O2 was 21.7 per cent of preconditioning V̇O2 peak values for WT horses. V̇O2 peak on the racetrack increased by 16.1 per cent from preconditioning to postconditioning in the WT horses (P=0.03), but did not change in the DT horses. Therefore, exercising horses in high water heights may improve conditioning.